PENAKSIR RASIO DAN PENAKSIR REGRESI YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN DEVIASI KUARTIL DAN KOEFISIEN SKEWNESS - Linda Veronika; Sigit Sugiarto; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article the combination of ratio estimators and  ratio-regression  in  simple random sampling  using  quartile  deviation  and coefficient of skewness are  discussed, which is a review from the  article  Jeelani  et.al.  [International Journal of Modern Mathematical Sciences,  6(3): 174-183]. These  estimators  are biased  estimators and  their  mean square errors are determined. Estimator with the smallest mean square error is the most efficient estimator. A numerical example is given at the end of discussion.